I conventi degli ordini mendicanti nel Montefeltro medievale Archeologia, tecniche di costruzione e decorazione plastica - Cerioni, Cristiano; DI CARPEGNA GABRIELLI FALCONIERI, Tommaso (Biblioteca di storia, 2012)
The remains in Montefeltro of the material structures of the medieval mendicant orders still constitute a fresh archive of data useful for casting light on the formal and technological transformations that took place in the first two centuries of its history. The book looks for the first time into the type of settlements of the Franciscan and Augustinian orders through the historical, archaeological, historico-artistic and petrographic analysis of the elevations of six convents dating from the thirteenth and fourteenth centuries.